Acupuncture for patients with mild hypertension: A randomized controlled trial. Issue 3 (8th February 2019) - Zheng, Hui; Li, Juan; Li, Ying; Zhao, Ling; Wu, Xi; Chen, Jie; Li, Xiang; Huang, Yin‐Lan; Chang, Xiao‐Rong; Liu, Mi; Cui, Jin; Wang, Rui‐Hui; et al.
Abstract : Acupuncture may be beneficial for patients with mild hypertension, but the evidence is not convincing. We aimed to examine the effect of acupuncture on blood pressure (BP) reduction in patients with mild hypertension. We conducted a multicenter, single‐blind, sham‐controlled, randomized trial in eleven hospitals in China. The trial included 428 patients with systolic blood pressure (SBP) from 140 to 159 mm Hg and/or with diastolic blood pressure (DBP) from 90 to 99 mm Hg. The patients were randomly assigned to receive 18 sessions of affected meridian acupuncture (n = 107) or non‐affected meridian acupuncture (n = 107) or sham acupuncture (n = 107) during 6 weeks, or to stay in a waiting‐list control (n = 107). All patients received 24‐hour ambulatory blood pressure monitoring at weeks 6, 9, and 12. We included 415 participants in the intention‐to‐treat analysis. The two acupuncture groups were pooled in the analysis, since they had no difference in all outcomes. SBP decreased at week 6 in acupuncture group vs sham acupuncture vs waiting‐list group (7.2 ± 11.0 mm Hg vs 4.1 ± 11.5 mm Hg vs 4.1 ± 13.2 mm Hg); acupuncture was not superior to sham acupuncture (mean difference 2.7 mm Hg, 95% CI 0.4 to 5.9, adjusted P = 0.103) or waiting‐list control (2.9 mm Hg, 95% CI −0.2 to 6.0, adjusted P = 0.078). However, acupuncture was superior to sham acupuncture (3.3 mm Hg, 95% CI 0.2 to 6.3, adjusted P = 0.035) and waiting‐list control (4.8 mm Hg, 95% CI 1.8 to 7.8, P < 0.001) at week 9. Acupuncture had a small effect size on the reduction of BP in patients with mild hypertension.